Pengendalian skabies dan pedikulosis melalui pengobatan dan penyuluhan perilaku hidup bersih dan sehat (PHBS) - Prasasty, Gita Dwi; Handayani, Dwi; Dalilah, Dalilah; Susilawati, Susilawati; Oktariana, Desi; Kristalia, Mareska Reggina; Khairani, Attina (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Neglected tropical diseases, including scabies and pediculosis, are diseases that are still a health problem in Indonesia. Islamic boarding schools are risky locations with a high prevalence of scabies and pediculosis because they have dense housing, lack of environmental sanitation and personal hygiene. This service activity aimed to increase knowledge about preventing and treating scabies and pediculosis in Pondok Pesantren X, South Sumatra. A total of 46 students with complaints of itching on the skin and head were present as participants in the activity which has been carried out in November 2023. The implementation of service consists of examination, counseling, as well as pretest and posttest. The scabies examination method was carried out clinically according to IACS 2020 criteria, while pediculosis examination was carried out with a serit combs. Counseling activities on the topic of clean and healthy living behavior was began and ended with the pretest and posttest. From the examination activities, it was found that 95% (44) students suffered scabies and 36% (17) students suffered pediculosis. Participants were quite enthusiastic in participating in counseling activities, as evidenced by the number of questions related to clean and healthy living behavior in daily activities at Islamic boarding schools. The counseling activity was quite successful, which can be seen from the increase in the correct value and significance (p < 0.05) of the pretest and posttest results.